Teaching Media of Fundamental Music Teaching: Multicultural of ASEAN Music - Thampitakkul , Ponglada (Journal of Education Studies, Chulalongkorn University, 2020)
Fundamental multicultural music teaching will enable learners to develop music knowledge, music skills and social culture of ASEAN countries. Appropriate music teaching media are needed. This research is qualitative research with the following objectives: 1) to study multicultural music teaching of ASEAN countries; 2) to analyze ASEAN music teaching media used in teaching fundamental music. Data from documents taken from the forum of ASEAN music education in 2012-2017 are studied and analyzed. The forum was organized by Department of Cultural Promotion of Ministry of Culture and Thailand Music Educators Association. All delegates are experts in music from educational institutions of ASEAN countries. The results show that: 1) multicultural ASEAN music teaching comprising of 6 musical activities: listening, singing, playing music, movement, reading and writing notations and musical creativity leads to understanding of knowledge in music and social culture of ASEAN music; 2) songs, musical instruments and music technology media are important in the teaching of fundamental music as they make learners understand music and social culture of ASEAN music.